Telehealth Therapy Effects of Nurses and Mental Health Professionals From 2 Randomized Controlled Trials for Chronic Back Pain. Issue 4 (April 2019) - Gannon, Jamie; Atkinson, Joseph H.; Chircop-Rollick, Tatiana; D'Andrea, John; Garfin, Steven; Patel, Shetal; Penzien, Donald B.; Wallace, Mark; Weickgenant, Anne L.; Slater, Mark; Holloway, Rachael; Rutledge, Thomas
Abstract : Objective: To compare the efficacy of mental health professional versus primary care nurse-delivered telehealth cognitive-behavioral therapy (CBT) and supportive care (SC) treatments for chronic low back pain, using data from 2 separate randomized controlled trials. Both trials were completed in the same hospital and used the same study design, research team, and outcome measures. Materials and Methods: Participants from Study 1 (Mental Health Professional Study) (N=66; 2007 to 2011) and Study 2 (Nursing Study) (N=61; 2012 to 2016) were patients with chronic low back pain (≥4/10 intensity) randomized to either an 8-week CBT or an SC telehealth condition matched for contact frequency, format, and time. Participants completed validated measures of improvement in back pain disability (Roland Morris Disability Questionnaire [RMDQ]), pain intensity (Numeric Rating Scale [NRS]), depressive symptoms (Beck Depression Inventory 2 [BDI-2]), pain catastrophizing (Pain Catastrophizing Scale [PCS]), and overall improvement (Global Clinical Impressions [GCI]). Results: Intent-to-treat analyses at posttreatment showed that scores on the RMDQ (Cohen d =0.33 to 0.55), NRS ( d =0.45 to 0.90), PCS ( d =0.21 to 0.41), and GCI (18.5% to 39.1%) improved significantly in both studies and in both treatments from pretreatment to posttreatment. Changes in BDI scores were inconsistent ( d =−0.06 to 0.51). The analyses revealed no significant differences in treatment efficacy between the trained nurse versus the mental health professionals on the RMDQ, NRS, PCS, or GCI measures ( P >0.20). Discussion: Results from these clinical trials suggest that the benefits of home-based, telehealth-delivered CBT and SC treatments for chronic back pain were comparable when delivered by a primary care nurse or mental health professional.